Use of ophthalmic artery Doppler in preeclampsia prognosis and early diagnostics - M. I. Melek; I. V. Ignatko; E. V. Timokhina; T. E. Kuzmina; I. A. Fedyunina; Yu. A. Samoilova; F. N. Alieva; I. S. Grigoryan; S. A. Podsekaeva (Акушерство, гинекология и репродукция)
Aim: to study ophthalmic artery blood flow parameters for predicting preeclampsia (РЕ) development, as well as compare prognostic value of their changes with calculated PE risk during prenatal screening.Materials and Methods. A prospective cohort comparative study was conducted by enrolling 80 pregnant women divided into two groups: per 40 subjects at high or low РЕ risk based on first-trimester prenatal screening assigned to main group and control group, respectively. Ophthalmic artery blood flow parameters (assessing the average magnitude from right and left examined vessels) was conducted from 11 to 13⁺⁶ weeks of pregnancy using Doppler ultrasound. Peak systolic velocity 1 (PSV1), peak systolic velocity 2 (PSV2), pulsatility index, and resistance index were assessed. Analysis of pregnancy course and outcomes was carried out.Results. In main group (high РЕ risk), 27 (67.5 %) patients had a normal course of pregnancy and term delivery (38–40 weeks). The remaining patients experienced hypertensive disorders and РЕ. Of the 40 women in main group, 25 (62.5 %) had vaginal deliveries, while 15 (37.5 %) underwent cesarean section (СS), 13 (86.7 %) subjects of those had indications related to РЕ and fetal growth restriction (FGR). In control group (low РЕ risk), 38 (95.0 %) women also had term delivery, with 31 (77.5 %) subjects having vaginal delivery and 9 (22.5 %) undergoing СS for indications unrelated to РЕ and FGR. Of the 80 patients from both study groups, РЕ developed in 10 (12.5 %) subjects: 2 cases (5.0 %) in low-risk PE group and 8 (20.0 %) in high-risk PE group. Early-onset РЕ (before 34 weeks of gestational age) was diagnosed in 2 patients (20.0 %) out of 10, whereas late-onset РE (after 34 weeks of gestational age) was diagnosed in 8 (80.0 %) subjects suggesting late PE predominance (ratio 1:4). PSV1 magnitude tended to insignificantly increase in control group. Pulsatility and resistance indices also did not reveal significant differences. In patients at high vs. low PE risk, the PSV2/PSV1 ratio was 8.0 % higher, but these differences were insignificant (p > 0.05), and among those pregnant women who developed PE, the PSV2/PSV1 ratio was significantly higher (p < 0.001) compared to group without PE.Conclusion. The study results evidence about the importance of evaluating ophthalmic artery blood flow parameters in pregnant women during the first prenatal screening as an additional tool for predicting PE.